A Pilot Investigation of a Novel Intervention to Improve Behavioral Well-Being for Children in Foster Care. (March 2019) - Wood, Joanne N.; Dougherty, Susan L.; Long, Jin; Messer, Erica P.; Rubin, David
Many studies have established a link between foster care placement instability and child behavioral problems. Evidence-based interventions for behavioral problems, however, are often unavailable to children in foster care given challenges of recruiting behavioral health providers, sustaining funding, and engaging families in intensive interventions. This pilot study, therefore, sought preliminary data on the effectiveness of a novel brief intervention, Child–Adult Relationship Enhancement (CARE), to decrease behavioral problems in children entering foster care. CARE, a trauma-informed 6-hr training, was implemented at two foster care agencies. Nineteen children, aged 3 to 8 years, newly entering foster care whose caregivers were exposed to CARE were compared with 28 historical comparison children from the same foster care agencies. Child behavioral problems were assessed at baseline and follow-up using the Child Behavior Checklist (CBCL). Adjusted CBCL change scores revealed greater improvements in externalizing and internalizing behaviors from baseline to follow-up among children in the CARE group compared with the historical comparison group (all p s ≤ .05). The effect was concentrated in younger children. Thus, CARE showed promise in improving parent-reported child behavior problems. The effectiveness of CARE needs to be further evaluated as it is replicated within child welfare systems.